Health and Wellness Coaching in Serving the Needs of Today's Patients: A Primer for Healthcare Professionals - Adam I Perlman MD, MPH; Abd Moain Abu Dabrh MBBCh, MS (SAGE Publishing, 2020)
The past six decades have been marked by leaps and bounds in medical advances, while concurrently clinical outcomes and the quality of life continued to lag or decline. There is a need for more comprehensive approaches to delivering healthcare to patients that address illness and wellness within and outside healthcare settings. Mounting evidence shows that making sustainable changes in healthcare requires approaching patients'/individuals' care as a continuum-within and outside healthcare settings-while addressing their capacity (ie ability) and workload (ie demands) and incorporating their values and preferences. Health and Wellness Coaching (HWC) has been proposed as a solution to create partnerships to empower individuals to take ownership, leadership, and accountability of their well-being, using nondirective, empathic, and mindful conversations that employ motivational-interviewing and evidence-based approaches. Insufficient clarity exists among healthcare professionals in understanding the definition, roles, and types of HWC. This primer summarizes HWC concepts and history and compares HWC types and its potential role in promoting, supporting, and improving the well-being, clinical outcomes, and quality of life of the pertinent stakeholders. This primer also highlights current and potential areas of application of HWC within different subpopulations and healthcare-related settings.